Physicochemical and thermal properties of Lignocellulosic fiber from Gigantochloa Scortechinii bamboo: effect of steam explosion treatment - Mat Darus, Siti Atiqa Al Zahra; Ghazali, Mariyam Jameelah; Azhari, Che Husna; Zulkifli, Rozli; Shamsuri, Ahmad Adlie; Sarac, Hanifi; Mustafa, Mohd Tamizi (Springer, 2020)
Bamboo is an abundant natural resource in Asia and one of the high potential fibers used to reinforce polymer composites. This article presents a comparative study on the physicochemical and thermal properties of bamboo fiber (BF) from Gigantochloa scortechinii for untreated BF, steam explosion (SE) treatment BF, and steam explosion followed by alkali (SE-alkali) treatment BF. The physicochemical and thermal properties of BF were determined using energy dispersive X-ray (EDX) spectroscopy and thermogravimetric analysis (TGA), while scanning electron microscopy (SEM) was used to examine the surfaces morphologies. A Fourier transform infrared (FTIR) spectroscopy was utilized to detect the presence of functional groups. TGA results showed that SE BF was significantly more thermally stable than the untreated BF and SE-alkali treatment BF. Major changes in chemical composition and surface morphology of the bamboo fibers indicated that hemicellulose and lignin were removed by SE-alkali treatment. In conclusion, the BF surface is physically and chemically modified by the SE-alkali treatment.